2015
DOI: 10.14336/ad.2015.0616
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine and Related Peptides: Therapeutic Potential in Age-Related Disorders

Abstract: Imidazole dipeptides (ID), such as carnosine (β-alanyl-L-histidine), are compounds widely distributed in excitable tissues of vertebrates. ID are also endowed of several biochemical properties in biological tissues, including antioxidant, bivalent metal ion chelating, proton buffering, and carbonyl scavenger activities. Furthermore, remarkable biological effects have been assigned to such compounds in age-related human disorders and in patients whose activity of serum carnosinase is deficient or undetectable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…In most instances, the beneficial effects of Car treatment were related to its generally ascribed antioxidant activity [31], which involves a capacity to decrease both ROS and RNS in different experimental models [32, 33]. In agreement with these and other studies, our experiments with cultured murine RAW 264.7 macrophages, using ME-LIF to detect the stable fluorescent NO adduct in cell lysates [27, 34], confirmed that Car decreases NO concentration in stimulated cells in a dose-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In most instances, the beneficial effects of Car treatment were related to its generally ascribed antioxidant activity [31], which involves a capacity to decrease both ROS and RNS in different experimental models [32, 33]. In agreement with these and other studies, our experiments with cultured murine RAW 264.7 macrophages, using ME-LIF to detect the stable fluorescent NO adduct in cell lysates [27, 34], confirmed that Car decreases NO concentration in stimulated cells in a dose-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of each SNP and dietary factor is small, the combined effect of the genetic and dietary factor is rather strong. CNDP1 and CNDP2 are dipeptidases that are related to the metabolism of carnosine or GSH, respectively [10,11,14,15], which are the most abundant naturally occurring endogenous dipeptide and tripeptide with antioxidant and free radical scavenger properties, respectively [11,12,13,16]. In addition, CNDP2 seems to be a Cys-Gly peptidase of the γ-glutamyl cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring endogenous dipeptides containing histidine, such as carnosine, anserine, and homocarnosine, have antioxidant and free radical scavenging properties [10,11,12]. Carnosine is the most abundant dipeptide and plays an important role in humans [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Admittedly, the topic is not without controversy [ 16 ], probably confounded by geographical (exposure to sunlight) and other factors. Furthermore, it has been suggested that carnosine is an anti-aging substance with a beneficial effect on the cardiovascular system [ 3 , 17 , 18 ]. There is, however, evidence that vegetarians have lower rates of coronary heart disease, hypertension, etc.…”
mentioning
confidence: 99%